HGG-26. TARGETABLE MOLECULAR ALTERATIONS IN CONGENITAL GLIOBLASTOMA. (23rd April 2019) - Gilani, Ahmed; Donson, Andrew; Whiteway, Susan; DeSisto, John; Hoffman, Lindsey; Foreman, Nicholas; Kleinschmidt-DeMasters, Bette K; Green, Adam
Abstract: BACKGROUND: Congenital glioblastomas (cGBM) are uncommon tumors presenting in early infancy (less than six months). Molecular features have not been not sufficiently explored due to the rarity of these tumors. We previously reported that cGBM appears similar to pediatric and adult GBM based on histology and microarray expression analysis but generally has a far more favorable outcome, with good responses to subtotal resection followed by moderate intensity chemotherapy (Neuro Oncol 14(7):931–41, July 2012). We thus explored other modalities of molecular analysis in an attempt to find an etiology for this difference in prognosis. METHODS: We performed molecular testing on a set of six cGBM samples from patients diagnosed at our institutions. We used Archer's FUSIONPlex Solid Tumor Kit, Illumina RNA-Seq, and next-generation sequencing of a panel of 25+ clinically relevant genes. RESULTS: The six cases represent four males and two females who underwent surgery between one and ten weeks of age. Three of the six cases analyzed showed fusions containing ALK (involving MAP4, MZT2B and EML4 as fusion partners), raising the potential for therapy with FDA-approved drugs lorlatinib or crizotinib. Of the remaining three, one case showed a ROS1 fusion, one had a mutation in heat shock protein gene HSPA1A, and one demonstrated a mutation in the transcriptional repressor gene CIC . None of the cases showed alterations in IDH1/2, histone 3 genes, NTRK, or TERT, alterations which are most commonly associated with pediatric and adult high-grade gliomas (HGG). CONCLUSIONS: These data show that cGBM are genetically heterogeneous and harbor alterations different from pediatric and adult HGG. Actionable fusions can frequently be identified.